PREVALENSI Candida albicans PADA PASIEN OTOMIKOSIS DI RSUD MARGONO SOEKARJO - Wijaya, Helmi Aditya; Darmawan, Anton Budhi; Nur Hestiyani, Rani Afifah; Krisniawati, Nia; Rujito, Lantip (Medical and Health Journal, 2023)
Background: Otomycosis is an infection of the ear caused by various fungi. One of the most common fungi that cause Otomycosis is Candida albicans. Otomycosis is a challenge for the medical world and patients because it requires long-term treatment and has a high recurrence rate. It causes the importance of an overview of the prevalence in a place as planning health services, description of cases, and eradication programs. Banyumas Regency has a climate that supports the growth of mushrooms. One of the major hospitals in Banyumas is RSUD Margono Soekarjo. Objective: Knew the prevalence of Candida albicans on Otomycosis at Margono Soekarjo Hospital. Method: This research is a descriptive observational study on the target population of patients at the ENT clinic at RSUD Margono Soekarjo—sampling technique using a total sampling of as many as 42 subjects with 46 samples. Data analysis techniques use univariate analysis to describe the characteristics of each variable. Results: The results of otomycosis sufferers at Margono Soekarjo Hospital were male compared to female by 50:50, namely 21 of 42 subjects (50.00%), respectively. The age group that suffered the most from Otomycosis was the 26-35 age group, with 12 out of 42 subjects (28.57%). The prevalence of Candida albicans in Otomycosis of 2.17% or 1 of 46 patient samples with a clinical diagnosis of Otomycosis at Margono Soekarjo Hospital was caused by a fungus Candida albicans. Conclusion: Prevalence Candida albicans as a cause of Otomycosis in patients at the ENT polyclinic at Margono Soekarjo Hospital in the Januari-February 2023 period of 2.17%, namely 1 out of 46 samples, with 26 years of age included in the 26-35 years age group and female.